1 Introduction
Let ${{\mathbf {U}}(\mathfrak {gl}_n)}$ be the quantized enveloping algebra of $\mathfrak {gl}_n$ over $\mathbb Q(v)$ (v an indeterminate) with Chevalley type generators $E_i$ , $F_i$ , and $K_j^{\pm 1}$ for $1\leqslant i\leqslant n-1$ and $1\leqslant j\leqslant n$ . Beilinson, Lusztig, and MacPherson (BLM) [Reference Beilinson, Lusztig and MacPherson3] constructed a realization for the quantum group ${{\mathbf {U}}(\mathfrak {gl}_n)}$ via a geometric setting of q-Schur algebras. A presentation of the q-Schur algebra ${\boldsymbol {\mathcal S}}(n,d)$ was given by Doty–Giaquinto [Reference Doty and Giaquinto8]. Du–Parshall [Reference Du and Parshall15] provided an approach to the $\mathfrak {sl}_n$ type presentation of the q-Schur algebra ${\boldsymbol {\mathcal S}}(n,d)$ using the Beilinson–Lusztig–MacPherson’s construction of ${{\mathbf {U}}(\mathfrak {gl}_n)}$ . The problem of describing the defining relations of a generalized q-Schur algebra as a quotient of a quantized enveloping algebra was investigated by Doty [Reference Doty7], Doty–Giaquinto–Sullivan [Reference Doty, Giaquinto and Sullivan9], [Reference Doty, Giaquinto and Sullivan10].
Infinitesimal Schur algebras are certain important subalgebras of Schur algebras (cf. [Reference Doty, Nakano and Peters11]). The polynomial representations of the group scheme $G_r T$ of degree d are equivalent to the representation theory of the infinitesimal Schur algebras . Here, $G_r$ is the r-th Frobenius kernel of the general linear group G over , and T is the subscheme of G arising from diagonal elements. A theory of the infinitesimal q-Schur algebra was studied by Cox [Reference Cox4], [Reference Cox5].
Let ${\mathcal Z}=\mathbb Z[v,v^{-1}]$ and be a commutative ring of characteristic p. Let be a primitive $l'$ th root of $1$ . We will regard as a ${\mathcal Z}$ -module by specializing v to $\varepsilon $ . Let , where ${U_{\mathcal Z}(\mathfrak {gl}_n)}$ is the ${\mathcal Z}$ -subalgebra of ${{\mathbf {U}}(\mathfrak {gl}_n)}$ generated by the elements $E_i^{(m)}$ , $F_i^{(m)}$ , $K_j^{\pm 1}$ , and $\big [ {K_j;0 \atop t} \big ]$ for $1\leqslant i\leqslant n-1$ , $1\leqslant j\leqslant n$ and $m,t\in \mathbb N$ . For $r\geqslant 1$ , let be the -subalgebra of generated by the elements $E_{i}^{(m)}$ , $F_{i}^{(m)}$ , $K_{j}^{\pm 1}$ , and $\big [{K_j;0 \atop t} \big ]$ for $1 \leqslant i \leqslant n-1$ , $1 \leqslant j \leqslant n$ , $t \in \mathbb {N}$ and $0 \leqslant m,t<l p^{r-1}$ , where $l=l'$ if $l'$ is odd, and $l=l'/2$ otherwise. Furthermore, let , where is the zero part of . Then, we have
and . In the case where $l'=l$ is an odd number, let
The algebra is the Lusztig’s small quantum group, and is called Frobenius–Lusztig kernels of (cf. [Reference Drupieski12], [Reference Lusztig22]). The representation theory of and was studied in [Reference Drupieski12].
Jimbo [Reference Jimbo20] proved that there is a natural surjective algebra homomorphism $\zeta _d$ from ${{\mathbf {U}}(\mathfrak {gl}_n)}$ to the q-Schur algebra ${\boldsymbol {\mathcal S}}(n,d)$ . The map $\zeta _d:{{\mathbf {U}}(\mathfrak {gl}_n)}\rightarrow {\boldsymbol {\mathcal S}}(n,d)$ induces a surjective algebra homomorphism
where is the infinitesimal q-Schur algebra over (cf. [Reference Fu18, Prop. 6.1]). Note that is a quotient algebra of in the case where $l'=l$ is odd. We prove in Theorem 4.10 that $\ker \zeta _{d,r}$ is generated by the elements $1-\sum _{\mu \in \Lambda (n,d)} K_{\mu }$ , $K_{i} K_{\lambda }-\varepsilon ^{\lambda _{i}} K_{\lambda }$ , $\big [{K_i;0 \atop t}\big ] K_{\lambda }-\big [{{\lambda }_i \atop t}\big ]_{\varepsilon } K_{\lambda }$ for $1 \leqslant i \leqslant n$ , $t \in \mathbb {N}$ and $\lambda \in \Lambda (n,d)$ , where $\Lambda (n,d)$ is the set of all compositions of d into n parts.
Let $\dot {{{\mathbf {U}}}}(\mathfrak {gl}_n)$ be the modified quantum group with generators $E_i1_{\lambda }$ , $1_{\lambda } F_i$ , and $1_{\lambda }$ for $1\leqslant i\leqslant n-1$ and ${\lambda }\in \mathbb Z^{n}$ . The map $\zeta _d:{{\mathbf {U}}(\mathfrak {gl}_n)}\rightarrow {\boldsymbol {\mathcal S}}(n,d)$ induces a surjective algebra homomorphism
Let , where $\dot {{U}}_{\mathcal Z}(\mathfrak {gl}_n)$ is the ${\mathcal Z}$ -subalgebra of $\dot {{{\mathbf {U}}}}(\mathfrak {gl}_n)$ generated by the elements $E_i^{(m)}1_{\lambda }$ , $1_{\lambda } F_i^{(m)}$ for $1\leqslant i\leqslant n-1$ , $m\in \mathbb N$ and ${\lambda }\in \mathbb Z^{n}$ . Let be the -subalgebra of generated by the elements $E_{i}^{(m)}1_{\lambda }$ and $1_{\lambda } F_{i}^{(m)}$ for $1 \leqslant i \leqslant n-1$ , $\lambda \in \mathbb Z^{n}$ and $0 \leqslant m<l p^{r-1}$ . The map $\dot {\zeta }_d:\dot {{{\mathbf {U}}}}(\mathfrak {gl}_n)\rightarrow {\boldsymbol {\mathcal S}}(n,d)$ induces a surjective algebra homomorphism
We prove in Theorem 5.5 that $\ker \dot {\zeta }_{d,r}$ is generated by the elements $1_{\lambda }$ for ${\lambda }\not \in \Lambda (n,d)$ .
The organization of the paper is as follows. We recall the BLM construction of the quantum group ${{\mathbf {U}}(\mathfrak {gl}_n)}$ in Section 2. In Section 3, we introduce the infinitesimal q-Schur algebra . A generating set for the kernel of the epimorphism is obtained in Section 4. In Section 5, we investigate the kernel of the epimorphism . In Section 6, we discuss the classical case. In Section 7, we investigate Borel subalgebras of the infinitesimal q-Schur algebra . As an application, we give a classification of irreducible -modules over a field of characteristic p in Section 8.
Throughout this paper, let ${\mathcal Z}=\mathbb Z[v,v^{-1}]$ where v is an indeterminate. For $i\in \mathbb Z$ let $[i]=\frac {v^i-v^{-i}}{v-v^{-1}}$ . For integers $N,t$ with $t\geqslant 0$ , let
where $[t]^{!}=[1][2]\cdots [t]$ .
Let be a commutative ring containing a primitive $l'$ th root $\varepsilon $ of $1$ with $l'\geqslant 1$ . Let $l\geqslant 1$ be defined by
Let p be the characteristic of . The commutative ring will be viewed as a ${\mathcal Z}$ -module by specializing v to $\varepsilon $ . For $c\in \mathbb Z$ and $t\in \mathbb N$ , we will denote the image of $\big [{c\atop t}\big ]\in {\mathcal Z}$ in by $\big [{c\atop t}\big ]_{\varepsilon }$ . For $\mu \in \mathbb Z^{n}$ and ${\lambda }\in \mathbb N^{n}$ let $\big [{\mu \atop {\lambda }}\big ]_{\varepsilon }=\big [{\mu _1\atop {\lambda }_1}\big ]_{\varepsilon }\cdots \big [{\mu _n\atop {\lambda }_n}\big ]_{\varepsilon }.$
2 The BLM construction of $ {{\mathbf {U}}(\mathfrak {gl}_n)} $
Following [Reference Jimbo20], we define the quantized enveloping algebra ${{\mathbf {U}}(\mathfrak {gl}_n)}$ of $\mathfrak {gl}_n$ to be the $\mathbb Q(v)$ algebra with generators
and relations
$\mathrm{(a)}\ K_{i}K_{j}=K_{j}K_{i},\ K_{i}K_{i}^{-1}=1;$
$\mathrm{(b)}\ K_{i}E_j=v^{\delta _{i,j}-\delta _{i,j+1}} E_jK_{i};$
$\mathrm{(c)}\ K_{i}F_j=v^{\delta _{i,j+1}-\delta _{i,j}} F_jK_{i};$
$\mathrm{(d)}\ E_iE_j=E_jE_i,\ F_iF_j=F_jF_i\ when\ |i-j|>1;$
$\mathrm{(e)}\ E_iF_j-F_jE_i=\delta _{i,j}\frac {\widetilde K_{i} -\widetilde K_{i}^{-1}}{v-v^{-1}},\ where \ \widetilde K_i =K_{i}K_{i+1}^{-1};$
$\mathrm{(f)}\ E_i^2E_j-(v+v^{-1})E_iE_jE_i+E_jE_i^2=0\ when\ |i-j|=1;$
$\mathrm{(g)}\ F_i^2F_j-(v+v^{-1})F_iF_jF_i+F_jF_i^2=0\ when\ |i-j|=1.$
Following [Reference Lusztig22], let ${U_{\mathcal Z}(\mathfrak {gl}_n)}$ be the Lusztig integral form of ${{\mathbf {U}}(\mathfrak {gl}_n)}$ generated by $E_{i}^{(m)}, F_{i}^{(m)}$ , $K_{j}^{\pm 1}$ , and $\big [{K_j;c \atop t}\big ](1 \leqslant i \leqslant n-1,1 \leqslant j \leqslant n, m, t \in \mathbb {N}, c \in \mathbb {Z})$ , where
with $[m]^{!}=[1][2] \cdots [m]$ and $[i]=\frac {v^{i}-v^{-i}}{v-v^{-1}}$ . The following result is given by Lusztig [Reference Lusztig21].
Lemma 2.1. The following formulas hold in ${U_{\mathcal Z}(\mathfrak {gl}_n)}:$
-
(1) $E_i^{(m)}\big [{K_j;c\atop t}\big ]=\big [{K_j;c+m(-\delta _{i,j}+\delta _{i+1,j})\atop t}\big ] E_i^{(m)};$
-
(2) $F_i^{(m)}\big [{K_j;c\atop t}\big ]=\big [{K_j;c-m(-\delta _{i,j}+\delta _{i+1,j})\atop t}\big ] F_i^{(m)};$
-
(3) For $k,l\in \mathbb N$ , we have
$$ \begin{align*}E_i^{(k)}F_i^{(l)}=\sum_{0\leqslant t\leqslant k\atop t\leqslant l}F_i^{(l-t)} \bigg[{\widetilde K_i;2t-k-l\atop t}\bigg]E_i^{(k-t)},\end{align*} $$where $\big [ {\widetilde K_i;c \atop t} \big ] = \prod _{s=1}^t \frac {\widetilde K_iv^{c-s+1}-\widetilde K_i^{-1}v^{-c+s-1}}{v^s-v^{-s}}$ .
Let $\Pi (n)=\{\alpha _i\mid 1\leqslant i\leqslant n-1\}$ , where $\alpha _i=\boldsymbol {e}_i-\boldsymbol {e}_{i+1}$ with $\boldsymbol e_i=(0,\ldots ,0,\underset i1,0\cdots ,0)\in \mathbb Z^n.$ We have the following direct sum decomposition:
where ${{\mathbf {U}}(\mathfrak {gl}_n)}_\nu $ is defined by the conditions ${{\mathbf {U}}(\mathfrak {gl}_n)}_{\nu '}{{\mathbf {U}}(\mathfrak {gl}_n)}_{\nu "}\subseteq {{\mathbf {U}}(\mathfrak {gl}_n)}_{\nu '+\nu "}$ , $K_j^{\pm 1}\in {{\mathbf {U}}(\mathfrak {gl}_n)}_0$ , $E_i\in {{\mathbf {U}}(\mathfrak {gl}_n)}_{\alpha _i}$ , $F_i\in {{\mathbf {U}}(\mathfrak {gl}_n)}_{-\alpha _i}$ for all $\nu ',\nu "\in \mathbb Z\Pi (n)$ , $1\leqslant i\leqslant n-1$ and $1\leqslant j\leqslant n$ .
Following [Reference Lusztig23, 23.1], we introduce the modified quantum group $\dot {{{\mathbf {U}}}}(\mathfrak {gl}_n)$ associated with ${{\mathbf {U}}(\mathfrak {gl}_n)}$ as follows. Let
where
and ${\lambda }\cdot {\mathbf {j}}=\sum _{1\leqslant i\leqslant n}{\lambda }_ij_i$ . Let $\pi _{{\lambda },\mu }: {{\mathbf {U}}(\mathfrak {gl}_n)}\rightarrow {}_{{\lambda }}{{\mathbf {U}}(\mathfrak {gl}_n)}_{\mu }$ be the canonical projection.
We define the product in $\dot {{{\mathbf {U}}}}(\mathfrak {gl}_n)$ as follows. For ${\lambda }', \mu ', {\lambda }", \mu " \in \mathbb Z^{n}$ with ${\lambda }'-\mu '$ , ${\lambda }"-\mu " \in \mathbb Z \Pi (n)$ and any $t \in {{\mathbf {U}}(\mathfrak {gl}_n)}_{{\lambda }'-\mu '}$ , $s \in {{\mathbf {U}}(\mathfrak {gl}_n)}_{{\lambda }"-\mu "}$ , define
Then $\dot {{{\mathbf {U}}}}(\mathfrak {gl}_n)$ becomes an associative $\mathbb Q(v)$ -algebra with the above product. Moreover, the algebra $\dot {{{\mathbf {U}}}}(\mathfrak {gl}_n)$ is naturally a ${{\mathbf {U}}(\mathfrak {gl}_n)}$ -bimodule defined by $t' \pi _{{\lambda }', {\lambda }"}(s) t"=\pi _{{\lambda }'+\nu ', {\lambda }"-\nu "}(t' s t")$ for $t' \in {{\mathbf {U}}(\mathfrak {gl}_n)}_{\nu '}, s \in {{\mathbf {U}}(\mathfrak {gl}_n)}, t" \in {{\mathbf {U}}(\mathfrak {gl}_n)}_{\nu "}$ , and ${\lambda }', {\lambda }" \in \mathbb Z^{n} .$ Let $\dot {{U}}_{\mathcal Z}(\mathfrak {gl}_n)$ be the ${\mathcal Z}$ -subalgebra of $\dot {{{\mathbf {U}}}}(\mathfrak {gl}_n)$ generated by the elements $E_{i}^{(m)} 1_{\lambda }$ and $1_{\lambda } F_{i}^{(m)}$ for $1 \leqslant i \leqslant n-1$ and $m \in \mathbb {N}$ , where $1_{\lambda }=\pi _{\lambda , \lambda }(1)$ .
We now follow [Reference Dipper and James6] to recall the definition of q-Schur algebras as follows. The Hecke algebra ${{\mathcal H}_{\mathcal Z}(d)}$ associated with ${\mathfrak S}_d$ is the ${\mathcal Z}$ -algebra generated by $T_i$ ( $1\leqslant i\leqslant d-1$ ), with the following relations:
where $q=v^2$ . Let ${\boldsymbol {\mathcal H}}(d)={{\mathcal H}_{\mathcal Z}(d)}\otimes _{\mathcal Z}\mathbb Q(v)$ . If $w=s_{i_1}s_{i_2}\cdots s_{i_m}$ is reduced let $T_w=T_{i_1}T_{i_2}\cdots T_{i_m}$ . Then the set $\{T_w\mid w\in {\mathfrak S}_d\}$ forms a ${\mathcal Z}$ -basis for ${{\mathcal H}_{\mathcal Z}(d)}$ . Let $\Lambda (n,d)=\{{\lambda }\in \mathbb N^{n}\mid \sigma ({\lambda })=d\}$ , where $\sigma ({\lambda })=\sum _{1\leqslant i\leqslant n}{\lambda }_i$ . For ${\lambda }\in \Lambda (n,d)$ , let $x_{{\lambda }}=\sum _{w\in {\mathfrak S}_{{\lambda }}}T_w$ , where ${\mathfrak S}_{{\lambda }}$ is the Young subgroup of ${\mathfrak S}_d$ . The endomorphism algebras
are called q-Schur algebras over ${\mathcal Z}$ and over $\mathbb Q(v)$ , respectively.
We now recall the BLM construction of ${{\mathbf {U}}(\mathfrak {gl}_n)}$ . Let $\widetilde {\Theta }(n)$ be the set of all $n \times n$ matrices over $\mathbb {Z}$ with all off diagonal entries in $\mathbb {N}$ . Let $\Theta (n)$ be the set of all $n\times n$ matrices over $\mathbb N$ . Let ${\Theta (n,d)}$ be the set of all $n \times n$ matrices A over $\mathbb {N}$ such that $\sigma (A)=d$ , where $\sigma (A)=\sum _{1 \leqslant i, j \leqslant n} a_{i, j}$ . For $A \in \widetilde {\Theta }(n)$ , let $\operatorname {ro}(A)=(\sum _{j} a_{1, j}, \ldots , \sum _{j} a_{n, j})$ and $\operatorname {co}(A)=$ $(\sum _{i} a_{i, 1}, \ldots , \sum _{i} a_{i, n})$ .
The q-Schur algebra ${\mathcal S}_{\mathcal Z}(n,d)$ was reconstructed using the geometry of pairs of n-step filtrations on a d-dimensional vector space in [Reference Beilinson, Lusztig and MacPherson3]. In particular, a normalized ${\mathcal Z}$ -basis $\{[A]\}_{A \in {\Theta (n,d)}}$ for ${\mathcal S}_{\mathcal Z}(n,d)$ was constructed. Using the stabilization property of multiplication for q-Schur algebra, an important ${\mathcal Z}$ -algebra $K_{\mathcal Z}(n)$ (without $ 1 $ ), with basis $\{[A]\}_{A \in \widetilde {\Theta }(n)} $ , was constructed in [1, §4]. Let ${\mathbf K}(n)=K_{\mathcal Z}(n)\otimes _{\mathcal Z}\mathbb Q(v)$ . Following [Reference Beilinson, Lusztig and MacPherson3, 5.1], we define $\widehat {{\mathbf K}}(n)$ to be the vector space of all formal (possibly infinite) $\mathbb {Q}(v)$ -linear combinations $\sum _{A \in \widetilde {\Theta }(n)} \beta _{A}[A]$ satisfying the following property: for any ${\mathbf {x}} \in \mathbb Z^{n}$ , the sets $\{A \in \widetilde {\Theta }(n) \mid \beta _{A} \neq 0, \operatorname {ro}(A)={\mathbf {x}}\}$ and $\{A \in \widetilde {\Theta }(n) \mid \beta _{A} \neq 0, \operatorname {co}(A)={\mathbf {x}}\}$ are finite. The product of two elements $\sum _{A \in \widetilde {\Theta }(n)} \beta _{A}[A]$ , $\sum _{B \in \widetilde {\Theta }(n)} \gamma _{B}[B]$ in $\widehat {{\mathbf K}}(n)$ is defined to be $\sum _{A, B} \beta _{A} \gamma _{B}[A] \cdot [B]$ , where $[A] \cdot [B]$ is the product in $K_{\mathcal Z}(n).$ Then $\widehat {{\mathbf K}}(n)$ is an associative algebra.
Let $\Theta ^\pm (n)$ be the set of all $A \in \Theta (n)$ such that all diagonal entries are zero. For $A \in \Theta ^\pm (n)$ and ${\mathbf {j}} \in \mathbb {Z}^{n}$ , let
where ${\lambda }\cdot{{\mathbf {j}}}=\sum _{1\leqslant i\leqslant n}{\lambda }_i{j_i}$ .
We shall denote by $\mathbf {V}(n)$ the subspace of $\widehat {{\mathbf K}}(n)$ spanned by the elements $A({\mathbf {j}})$ for $A \in \Theta ^{\pm }(n)$ and ${\mathbf {j}} \in \mathbb {Z}^{n}$ . For $1 \leqslant i, j \leqslant n$ , let $E_{i, j} \in \Theta (n)$ be the matrix whose $(i,j)$ -entry is $1$ and the other entries are $0$ . The following result was given by Beilinson–Lusztig–MacPherson [Reference Beilinson, Lusztig and MacPherson3].
Theorem 2.2. $(1)$ $\mathbf {V}(n)$ is a subalgebra of $\widehat {{\mathbf K}}(n)$ and there is an algebra isomorphism ${{\mathbf {U}}(\mathfrak {gl}_n)}\stackrel {\thicksim }{\,\rightarrow }\mathbf {V}(n)$ satisfying
$(2)$ There is an algebra epimorphism $\zeta _d:{{\mathbf {U}}(\mathfrak {gl}_n)}\rightarrow {\boldsymbol {\mathcal S}}(n,d)$ satisfying
We shall identify ${{\mathbf {U}}(\mathfrak {gl}_n)}$ with $\mathbf {V}(n)$ . By [Reference Du and Fu14] we have the following result (cf. [Reference Fu17]).
Lemma 2.3. $(1)$ There is an algebra isomorphism $\varphi :\dot {{{\mathbf {U}}}}(\mathfrak {gl}_n)\rightarrow {\mathbf K}(n)$ satisfying
for all $u\in {{\mathbf {U}}(\mathfrak {gl}_n)}$ and ${\lambda },\mu \in \mathbb Z^{n}$ . Furthermore, we have $\varphi (\dot {{U}}_{\mathcal Z}(\mathfrak {gl}_n))=K_{\mathcal Z}(n)$ .
$(2)$ There is a surjective algebra homomorphism $\dot {\zeta }_d:{\mathbf K}(n)\rightarrow {\boldsymbol {\mathcal S}}(n,d)$ such that
We shall identify $\dot {{U}}_{\mathcal Z}(\mathfrak {gl}_n)$ with $K_{\mathcal Z}(n)$ .
3 The infinitesimal q-Schur algebra
Let . We shall denote the images of $E_{i}^{(m)}, F_{i}^{(m)}$ , etc. in by the same letters. Let (resp. ) be the subalgebra of generated by the elements $E_{i}^{(m)}$ (resp. $F_{i}^{(m)}$ ) for $1\leqslant i\leqslant n-1$ and $m\in \mathbb N$ . Let be the subalgebra of generated by the elements $K_{j}^{\pm 1}$ and $\big [{K_j;0 \atop t} \big ]$ for $1 \leqslant j \leqslant n$ and $t \in \mathbb {N}$ . Then we have . The algebras and are both $\mathbb {N}$ -graded in terms of the degrees of monomials in the $E_{i}^{(m)}$ and $F_{i}^{(m)}$ .
For $r\geqslant 1$ , let be the -subalgebra of generated by the elements $E_{i}^{(m)}$ , $F_{i}^{(m)}$ , $K_{j}^{\pm 1}$ , and $\big [{K_j;0 \atop t} \big ]$ for $1 \leqslant i \leqslant n-1$ , $1 \leqslant j \leqslant n$ , $t \in \mathbb {N}$ and $0 \leqslant m,t<l p^{r-1}$ . Furthermore, let
Clearly, the algebra is a Hopf subalgebra of . Let (resp. ) be the subalgebra of generated by the elements $E_{i}^{(m)}$ (resp. $F_{i}^{(m)}$ ) for $1\leqslant i\leqslant n-1$ and $0 \leqslant m<l p^{r-1}$ . Then we have .
Let $\Theta ^+(n)=\left \{A \in \Theta (n) \mid a_{i, j}=0, \forall i \geqslant j\right \}$ and $\Theta ^-(n)=\left \{A \in \Theta (n) \mid a_{i, j}=0, \forall i \leqslant j\right \}$ . For $A \in \widetilde \Theta (n)$ , write $A=A^{+}+\operatorname {diag}({\lambda })+A^{-}$ with $A^{+} \in \Theta ^+(n)$ , $A^{-} \in \Theta ^-(n)$ and ${\lambda }\in \mathbb Z^{n}$ . Let
Let
For $A \in \Theta ^\pm (n)_r$ , let
where
and
For $A \in \Theta ^\pm (n)$ let
Then we have $\textrm {deg}(E^{(A^+)})=\textrm {deg}(A^+)$ and $\textrm {deg}(F^{(A^-)})=\textrm { deg}(A^-)$ for $A\in \Theta ^\pm (n)$ . For ${\lambda }\in \mathbb N^{n}$ and ${\mathbf {j}}\in \mathbb Z^{n}$ let
The following result is given in [Reference Fu18, Lem. 6.3].
Proposition 3.1. $(1)$ The set $\big \{E^{(A^+)} K^\delta K_{\lambda } F^{(A^-)} \mid A \in \Theta ^\pm (n)_r,\, \delta ,{\lambda } \in \mathbb N^{n},\, \delta _{i} \in \{0,1\},\,\forall i\big \}$ forms a -basis for .
$(2)$ The set $\big \{E^{(A^+)} \mid A \in \Theta ^+(n)_r\}$ (resp. $\big \{F^{(A^-)} \mid A \in \Theta ^-(n)_r\}$ ) forms a -basis for (resp. ).
For $A\in \widetilde \Theta (n)$ let
Following [Reference Beilinson, Lusztig and MacPherson3], for $A,B\in \widetilde \Theta (n)$ , define $B \preccurlyeq A$ if and only if $\sigma _{i,j}( B )\leqslant \sigma _{i,j}(A)$ for all $i\not =j$ . Put $ B \prec A$ if $ B \preccurlyeq A$ and $\sigma _{i,j}( B )<\sigma _{i,j}(A)$ for some $i\not =j$ .
Proposition 3.2. $(1)$ The set $\big \{A^+(\mathbf {0}) K^\delta K_{\lambda } A^-(\mathbf {0}) \mid A \in \Theta ^\pm (n)_r,\,\delta ,\lambda \in \mathbb {N}^{n},\, \delta _{i} \in \{0,1\}, \forall i \big \}$ forms a -basis for .
$(2)$ The set $\big \{A(\mathbf {0}) \mid A \in \Theta ^+(n)_r\}$ (resp. $\big \{A(\mathbf {0}) \mid A \in \Theta ^-(n)_r\}$ ) forms a -basis for (resp. ).
Proof. By [Reference Beilinson, Lusztig and MacPherson3, 4.6(c)] for $A \in \Theta ^\pm (n)_r$ , we have
where f is a -linear combination of $B(\mathbf {0})$ for $B\in \Theta ^+(n)$ with $B\prec A^+$ and g is a -linear combination of $C(\mathbf {0})$ for $C\in \Theta ^-(n)$ with $C\prec A^-$ . By [Reference Fu18, Lem. 6.3] we know that f must a -linear combination of $B(\mathbf {0})$ for $B\in \Theta ^+(n)_r$ with $B\prec A^+$ and g is a -linear combination of $C(\mathbf {0})$ for $C\in \Theta ^-(n)_r$ with $C\prec A^-$ . Now the assertion follows from Proposition 3.1.
Let . We shall denote the images of $E_{i}^{(m)}1_{\lambda }$ , $1_{\lambda } F_{i}^{(m)}$ , $E^{(A^+)} 1_{\lambda }$ , $1_{\lambda }F^{(A^-)}$ in by the same letters. For $A\in \widetilde \Theta (n)$ let
Let be the -subalgebra of generated by the elements $E_{i}^{(m)}1_{\lambda }$ and $1_{\lambda } F_{i}^{(m)}$ for $1 \leqslant i \leqslant n-1$ , $\lambda \in \mathbb Z^{n}$ and $0 \leqslant m<l p^{r-1}$ .
For $ A \in \widetilde \Theta (n)$ and $1 \leqslant i \leqslant n$ , let
where $ \sigma _{i}(A)=a_{i,i}+\sum _{1 \leqslant j<i}(a_{i j}+a_{j i})$ . Let
We have the following monomial, BLM and PBW bases of .
Proposition 3.3. Each of the following sets forms a -basis of :
-
(1) ${\mathscr M}_r:=\{E^{(A^+)} 1_{{\boldsymbol \sigma }(A)} F^{(A^-)} \mid A\in \widetilde \Theta (n)_r\};$
-
(2) ${\mathscr L}_r:=\{[A]_{\varepsilon }\mid A\in \widetilde \Theta (n)_r\};$
-
(3) ${\mathscr P}_r:=\{A^+(\mathbf {0}) 1_{{\boldsymbol \sigma }(A)} A^-(\mathbf {0}) \mid A\in \widetilde \Theta (n)_r\}$ .
Proof. Let be the -submodule of spanned by the elements $[A]_{\varepsilon }$ for $A\in \widetilde \Theta (n)_r$ . By [Reference Beilinson, Lusztig and MacPherson3, 4.6(a)] for $1\leqslant h\leqslant n-1$ , $0\leqslant m<lp^{r-1}$ , $A\in \widetilde \Theta (n)_r$ , we have
where $\beta ({\mathbf {t}})=\sum _{j> u}(a_{h,j}-a_{h+1,j})t_u+\sum _{u<u'}t_ut_{u'}$ . If $A+\sum _{u}t_u(E_{h,u}-E_{h+1,u})\not \in \widetilde \Theta (n)_r$ for some ${\mathbf {t}}\in \Lambda (n,m)$ , then we have $a_{h,u}+t_u\geqslant lp^{r-1}$ for some $u\not =h$ . Since $A\in \widetilde \Theta (n)_r$ , ${\mathbf {t}}\in \Lambda (n,m)$ and $m<lp^{r-1}$ , we have $a_{h,u}<lp^{r-1}$ and $t_u<lp^{r-1}$ . Hence, by [Reference Fu18, Cor. 3.4] we have $\big [{a_{h,u}+t_u\atop t_u}\big ]_{\varepsilon }=0$ . Therefore, we have
Similarly, we have
for $1\leqslant h\leqslant n-1$ and $0\leqslant m<lp^{r-1}$ . Consequently, we have
Furthermore, by [Reference Beilinson, Lusztig and MacPherson3, 4.6(c)] for $A \in \widetilde \Theta (n)_r$ ,
where f is a -linear combination of $[B]_{\varepsilon }$ for $B\in \widetilde \Theta (n)$ with $B\prec A$ . By (3.3), we see that f must be a -linear combination of $[B]_{\varepsilon }$ for $B\in \widetilde \Theta (n)_r$ with $B\prec A$ . It follows from (3.2) that
where g is a -linear combination of $[B]_{\varepsilon }$ for $B\in \widetilde \Theta (n)_r$ with $B\prec A$ . Therefore, each of the sets ${\mathscr M}_r$ , ${\mathscr L}_r$ , ${\mathscr P}_r$ forms a -basis of and
Hence, by (3.3) we have . The proof is completed.
Let . By [Reference Du13] we have $\zeta _d({U_{\mathcal Z}(\mathfrak {gl}_n)})={\mathcal S}_{\mathcal Z}(n,d)$ . Therefore, the map $\zeta _d: {{\mathbf {U}}(\mathfrak {gl}_n)} \rightarrow {\boldsymbol {\mathcal S}}(n,d)$ given in Theorem 2.2 restricts to a surjective algebra homomorphism
A generating set for the kernel of $\zeta _{d}:{U_{\mathcal Z}(\mathfrak {gl}_n)} \rightarrow {\mathcal S}_{\mathcal Z}(n,d)$ was given in [Reference Fu and Gao19]. The map $\zeta _{d}$ induces, upon tensoring with , a surjective algebra homomorphism
Let
for $1 \leqslant i \leqslant n-1$ and $1\leqslant j \leqslant n$ . For $A \in \Theta (n)$ and ${\lambda }\in \mathbb N^{n} $ , let
For $ A \in {\Theta (n,d)}$ , let
By [Reference Du and Parshall15, Cor. 5.3], we have
for ${\lambda }\in \Lambda (n,d)$ .
Let be the infinitesimal q-Schur algebra introduced in [Reference Cox4]. The algebra is a -subalgebra of the q-Schur algebra . Let
According to [Reference Cox4, 5.3.1] and the proof of [Reference Fu16, Th. 5.5], we have the following result.
Lemma 3.4. The set ${\mathscr L}_{d,r}:=\{[A]_{\varepsilon } \mid A \in \Theta (n,d)_r\}$ forms a -basis of .
By [Reference Fu18, Prop. 6.4], we have the following result.
Lemma 3.5. For $d\in \mathbb N$ we have
The map $\dot {\zeta }_d: \dot {{{\mathbf {U}}}}(\mathfrak {gl}_n)={\mathbf K}(n)\rightarrow {\boldsymbol {\mathcal S}}(n,d)$ given in Lemma 2.3 restricts to a surjective algebra homomorphism
tensoring with , we obtain a surjective algebra homomorphism
Combining Lemma 2.3 with Proposition 3.3, we obtain the following result.
Lemma 3.6. For $d\in \mathbb N$ we have .
For ${\lambda },\mu \in \mathbb Z^{n}$ , write ${\lambda }\leqslant \mu \Leftrightarrow {\lambda }_i\leqslant \mu _i$ for $1\leqslant i\leqslant n$ . We have the following monomial and PBW bases of .
Proposition 3.7. Each of the following set forms a -basis of :
-
(1) ${\mathscr M}_{d,r}=\{{\mathtt e}^{(A^+)}\mathtt {k}_{{\lambda }} {\mathtt f}^{(A^-)} \mid A \in \Theta ^\pm (n)_r,\,{\lambda }\in \Lambda (n,d),\,{\lambda }\geqslant {\boldsymbol \sigma }(A)\};$
-
(2) ${\mathscr P}_{d,r}=\{A^+(\mathbf {0},d) \mathtt {k}_{{\lambda }} A^-(\mathbf {0},d) \mid A \in \Theta ^\pm (n)_r,\,{\lambda }\in \Lambda (n,d),\,{\lambda }\geqslant {\boldsymbol \sigma }(A)\}.$
Proof. By Lemma 2.3, (3.4), (3.5), and (3.8), for $A \in \Theta ^\pm (n)_r$ , ${\lambda }\in \Lambda (n,d)$ with ${\lambda }\geqslant {\boldsymbol \sigma }(A)$ , we have
where . Now the assertion follows from Lemma 3.4.
4 The algebra
For $d\in \mathbb N$ let
where $I_{d,r}$ is the two-sided ideal of generated by the elements $1-\sum _{\mu \in \Lambda (n,d)} K_{\mu }$ , $K_{i} K_{\lambda }-\varepsilon ^{\lambda _{i}} K_{\lambda }$ and $\big [{K_i;0 \atop t}\big ] K_{\lambda }-\big [{{\lambda }_i \atop t}\big ]_{\varepsilon } K_{\lambda }$ for $1 \leqslant i \leqslant n$ , $t \in \mathbb {N}$ and $\lambda \in \Lambda (n,d)$ . For $1\leqslant i\leqslant n-1$ , $t\in \mathbb N$ and $0\leqslant m<lp^{r-1}$ let
Furthermore, for $1\leqslant j\leqslant n$ , $c\in \mathbb Z$ , $t\in \mathbb N$ and ${\lambda }\in \mathbb N^{n}$ let
We will prove in Theorem 4.10 that the algebra is isomorphic to the infinitesimal q-Schur algebra .
Lemma 4.1. $(1)$ For ${\lambda },\mu \in \Lambda (n,d)$ we have $\mathbf {k}_{\lambda }\mathbf {k}_\mu =\delta _{{\lambda },\mu }\mathbf {k}_{\lambda }$ .
$(2)$ Assume $\nu \in \mathbb N^{n}$ is such that $\sigma (\nu )>d$ . Then we have $\mathbf {k}_\nu =0$ .
Proof. For $1\leqslant i\leqslant n$ and $t\in \mathbb N$ , we have $\big [{\mathbf {k}_i;0 \atop t}\big ]\mathbf {k}_\mu = \big [{ \mu _i\atop t}\big ]_{\varepsilon } \mathbf {k}_\mu $ . It follows that
If $\big [{ \mu \atop {\lambda }}\big ]_{\varepsilon }\not =0$ , then we have $\mu \geqslant {\lambda }$ . This implies that $\mu ={\lambda }$ since ${\lambda },\mu \in \Lambda (n,d)$ . Therefore, we have $\mathbf {k}_{\lambda }\mathbf {k}_\mu =\delta _{{\lambda },\mu }\mathbf {k}_{\lambda }$ . Furthermore, since $1=\sum _{{\gamma } \in \Lambda (n,d)}\mathbf {k}_{\gamma }$ and $\sigma (\nu )>d$ , we have
The proof is completed.
For $a,b\in \mathbb Z$ , we have
Lemma 4.2. Let ${\lambda }\in \Lambda (n,d)$ . Then we have $\big [{\mathbf {k}_i;c\atop t}\big ] \mathbf {k}_{\lambda }=\big [{{\lambda }_i+c\atop t}\big ]_{\varepsilon } \mathbf {k}_{\lambda }$ for $1\leqslant i\leqslant n$ , $c\in \mathbb Z$ , $t\in \mathbb N$ .
Proof. Assume $c\geqslant 0$ . By [Reference Lusztig22, 2.3 (g9), (g10)], we have
Hence, by (4.1), we have
The proof is completed.
By the definition of , we have the following result.
Lemma 4.3. There is an algebra anti-automorphism $\tau _d$ on such that
for $1\leqslant i \leqslant n-1$ , $1\leqslant j \leqslant n$ , $t\in \mathbb N$ and $0\leqslant m<lp^{r-1}$ .
Lemma 4.4. Let ${\lambda },\mu \in \Lambda (n,d)$ and $a\in \mathbb N$ .
$(1)$ If ${\lambda }_{i+1}<a$ for some $1\leqslant i \leqslant n-1$ , then we have $\mathbf {e}_i^{(a)}\mathbf {k}_{\lambda }=\mathbf {k}_{\lambda }\mathbf {f}_i^{(a)}=0$ .
$(2)$ If $\mu _{j}<a$ for some $1\leqslant j \leqslant n-1$ , then we have $\mathbf {k}_\mu \mathbf {e}_j^{(a)}=\mathbf {f}_j^{(a)}\mathbf {k}_\mu =0$ .
Proof. By Lemma 2.1 and 4.2, we have
Hence, by Lemma 4.1 we have $\mathbf {k}_{{\lambda }+a\boldsymbol {e}_i-{\lambda }_{i+1}\boldsymbol {e}_{i+1}}=0$ and $\mathbf {k}_{{\lambda }+a\boldsymbol {e}_{j+1}-\mu _j\boldsymbol {e}_j}=0$ , since ${\lambda }_{i+1}<a$ , $\mu _j<a$ and ${\lambda },\mu \in \Lambda (n,d)$ . Therefore we have $\mathbf {e}_i^{(a)}\mathbf {k}_{\lambda }=\mathbf {k}_\mu \mathbf {e}_j^{(a)}=0$ . Consequently, we have $\mathbf {k}_{\lambda }\mathbf {f}_i^{(a)}=\tau _d(\mathbf {e}_i^{(a)}\mathbf {k}_{\lambda })=0$ and $\mathbf {f}_j^{(a)}\mathbf {k}_\mu =\tau _d(\mathbf {k}_\mu \mathbf {e}_j^{(a)})=0$ .
Lemma 4.5. Let ${\lambda } \in \Lambda (n,d)$ and $a\in \mathbb N$ . If ${\lambda }_{i+1}\geqslant a$ for some $1\leqslant i \leqslant n-1$ , then we have $\mathbf {e}_i^{(a)}\mathbf {k}_{\lambda }=\mathbf {k}_{{\lambda }+a\alpha _i}\mathbf {e}_i^{(a)}$ and $\mathbf {k}_{\lambda }\mathbf {f}_i^{(a)}=\mathbf {f}_i^{(a)}\mathbf {k}_{{\lambda }+a\alpha _i}$ , where $\alpha _i=\boldsymbol {e}_i-\boldsymbol {e}_{i+1}$ .
Proof. By Lemma 2.1 and 4.2, we have
Hence, by Lemma 4.4, we have
Therefore, we have $\mathbf {k}_{\lambda }\mathbf {f}_i^{(a)}=\tau _d(\mathbf {e}_i^{(a)}\mathbf {k}_{\lambda })= \tau _d(\mathbf {k}_{{\lambda }+a\alpha _i} \mathbf {e}_i^{(a)} )=\mathbf {f}_i^{(a)}\mathbf {k}_{{\lambda }+a\alpha _i}$ .
For simplicity, we set $\mathbf {k}_{\lambda }=0$ if ${\lambda }\not \in \mathbb N^{n}$ with $\sigma ({\lambda })=d$ , where $\sigma ({\lambda })=\sum _{1\leqslant i\leqslant n}{\lambda }_i$ . Then, by Lemma 4.4 and 4.5, we have the following result.
Lemma 4.6. For ${\lambda } \in \mathbb Z^{n}$ with $\sigma ({\lambda })=d$ and $a\in \mathbb N$ we have $\mathbf {e}_i^{(a)}\mathbf {k}_{\lambda }=\mathbf {k}_{{\lambda }+a\alpha _i}\mathbf {e}_i^{(a)}$ and $\mathbf {k}_{\lambda }\mathbf {f}_i^{(a)}=\mathbf {f}_i^{(a)}\mathbf {k}_{{\lambda }+a\alpha _i}$ .
For $A\in \Theta ^\pm (n)$ let $\mathbf {e}^{(A^+)}=E^{(A^+)}+I_{d,r}$ and $\mathbf {f}^{(A^-)}=F^{(A^-)}+I_{d,r}$ .
Lemma 4.7. Let $A\in \Theta ^\pm (n)_r$ and ${\lambda } \in \mathbb Z^{n}$ with $\sigma ({\lambda })=d$ . Then, we have $\mathbf {e}^{(A^+)}\mathbf {k}_{\lambda }=\mathbf { k}_{{\lambda }-\textrm {co}(A^+)+\textrm {ro}(A^+)}\mathbf {e}^{(A^+)}$ and $\mathbf {k}_{\lambda }\mathbf {f}^{(A^-)}= \mathbf {f}^{(A^-)}\mathbf {k}_{{\lambda }+\textrm {co}(A^-)-\textrm {ro}(A^-)}$ .
Proof. By Lemma 4.6, we have $ \mathbf {e}^{(A^+)}\mathbf {k}_{\lambda }=\mathbf {k}_\mu \mathbf {e}^{(A^+)}$ and $\mathbf {k}_{\lambda }\mathbf {f}^{(A^-)}=\mathbf {f}^{(A^-)}\mathbf {k}_\nu $ where
and
The proof is completed.
Recall the sets $\Theta ^+(n)_r$ and $\Theta ^-(n)_r$ defined in (3.1).
Lemma 4.8. Let ${\lambda } \in \Lambda (n,d)$ .
-
(1) If $A \in \Theta ^+(n)_r$ and ${\lambda }_i<\sigma _i(A)$ for some i, then we have $\mathbf {e}^{(A)}\mathbf {k}_{\lambda }=0$ .
-
(2) If $A \in \Theta ^-(n)_r$ and ${\lambda }_i<\sigma _i(A)$ for some i, then we have $\mathbf {k}_{\lambda }\mathbf {f}^{(A)}=0$ .
Proof. If $A \in \Theta ^+(n)_r$ and ${\lambda }_i<\sigma _i(A)$ for some i, then by Lemma 4.6 we have
where $\mathbf {m}_j=\mathbf {e}^{(a_{j-1,j})}_{j-1}(\mathbf {e}_{j-2}^{(a_{j-2, j})} \mathbf {e}_{j-1}^{(a_{j-2, j})}) \cdots (\mathbf {e}_{1}^{(a_{1, j})} \mathbf { e}_{2}^{(a_{1, j})} \cdots \mathbf {e}_{j-1}^{(a_{1, j})})$ and
Since $\mu _i={\lambda }_i-\sigma _i(A)<0$ we have $\mathbf {k}_\mu =0$ . Hence, we have $\mathbf {e}^{(A)}\mathbf {k}_{\lambda }=0$ . Assume now that $A \in \Theta ^-(n)_r$ and ${\lambda }_i<\sigma _i(A)$ for some i. Then, we have $\mathbf {k}_{\lambda }\mathbf {f}^{(A)}=\tau _d(\mathbf {e}^{({}^tA)}\mathbf {k}_{\lambda })=0$ . The proof is completed.
For $A \in \Theta ^\pm (n)_r$ and ${\lambda } \in \Lambda (n,d)$ , let
Proposition 4.9. The set $\mathbf {M}_{d,r}=\{\mathbf {m}^{(A,{\lambda })}| A \in \Theta ^\pm (n)_r,\, {\lambda } \in \Lambda (n,d),\, {\lambda }\geqslant {\boldsymbol \sigma }(A)\}$ is a spanning set for .
Proof. By the definition of $I_{d,r}$ we have $\mathbf {k}_i=\sum _{{\lambda }\in \Lambda (n,d)}\varepsilon ^{{\lambda }_i}\mathbf {k}_{\lambda }$ and $\mathbf {k}_{\lambda }=\sum _{\mu \in \Lambda (n,d)} \big [{\mu \atop {\lambda }}\big ]_{\varepsilon }\mathbf {k}_\mu $ for ${\lambda }\in \Lambda (n,d)$ and $1\leqslant i\leqslant n$ . Hence, by Proposition 3.1, we see that the algebra is spanned by the elements $\mathbf {e}^{(A^+)} \mathbf {k}_{\lambda } \mathbf {f}^{(A^-)}$ for $A\in \Theta ^\pm (n)_r$ and $\lambda \in \Lambda (n,d)$ . Therefore, to prove the proposition, we have to show that if ${\lambda }_i< \sigma _i(A)$ for some i, then $\mathbf {m}^{(A,{\lambda })}$ lies in the span of $\mathbf {M}_{d,r}$ .
We argue by induction on $\textrm {deg}(A)$ . The result follows from Lemma 4.4 in the cases where $\textrm {deg}(A)=1$ . Assume now that $\textrm {deg}(A)>1$ , and suppose ${\lambda }_i<\sigma _i(A)$ for some $1\leqslant i\leqslant n$ . For $2\leqslant j\leqslant n$ let
Then, we have $\mathbf {e}^{(A^+)} =\mathbf {m}_n\mathbf {m}_{n-1}\cdots \mathbf {m}_2$ and $\mathbf {f}^{(A^-)} =\mathbf {m}_2^{\prime }\mathbf {m}_{3}^{\prime }\cdots \mathbf {m}_n'$ . Let $A_i$ be the submatrix of A consisting of the first i rows and columns, and write $\mathbf {e}^{(A^+)}=\mathbf {x}_1 \mathbf {e}^{(A_i^{+})}, \mathbf { f}^{(A^-)}=\mathbf {f}^{(A_i^-)}\mathbf {x}_1^\prime $ . Then,
where $\mathbf {x}_1=\mathbf {m}_n\mathbf {m}_{n-1}\cdots \mathbf {m}_{i+1}$ and $\mathbf {x}_1^{\prime }=\mathbf {m}_{i+1}^{\prime }\mathbf {m}_{i+2}^{\prime }\cdots \mathbf {m}_{n}^{\prime }$ . By Lemma 4.8, we may assume that ${\lambda }_i\geqslant \sigma _i(A_i^{+})=\sigma _i(A^{+})$ . Furthermore, by Lemma 4.7, we have
where ${\lambda }^\prime ={\lambda }-\textrm {co}(A_i^{+})+\textrm {ro}(A_i^+)$ . By Lemma 2.1,
where f is a -linear combination of $\mathbf {x}_j^{\mathbf {e}}\mathbf {h}_j \mathbf {x}^{\mathbf {f}}_j$ with and $\textrm {deg}(\mathbf {x}_j^{\mathbf {e}})+\textrm {deg} (\mathbf {x}_j^{\mathbf { f}}) < \textrm {deg}(A_i)$ . Here, $\mathbf {x}_j^{\mathbf {e}}$ (resp. $\mathbf {x}_j^{\mathbf {f}}$ ) denotes a monomial in the $\mathbf {e}_i^{(a)}$ (resp. $\mathbf {f}_i^{(a)}$ ). Thus, $\textrm {deg}(\mathbf {x}_1)+\textrm {deg}(\mathbf {x}_j^{\mathbf {e}})+\textrm {deg}(\mathbf {x}^{\mathbf {f}}_j)+\textrm {deg}(\mathbf {x}_1')<\textrm {deg}(A)$ . Since ${\lambda }_i<\sigma _i(A)$ , we have ${\lambda }_i^{\prime }={\lambda }_i-\sigma _i(A_i^+)<\sigma _i(A)-\sigma _i(A_i^+)=\sigma _i(A_i^-)$ . It follows from Lemma 4.7 that $ \mathbf {k}_{{\lambda }'}\mathbf {f}^{(A_i^-)}=0$ . Hence, we have
Furthermore, by Proposition 3.1, we see that each $\mathbf {x}_1\mathbf {x}_j^{\mathbf {e}}$ is a -linear combination of $\mathbf { e}^{(B)}$ with $B\in \Theta ^+(n)_r$ , $\textrm {deg}(B)=\textrm {deg}(\mathbf {x}_1\mathbf {x}_j^{\mathbf {e}})$ and each $\mathbf {x}_j^{\mathbf {f}} \mathbf {x}_1^\prime $ is a -linear combination of $\mathbf {f}^{(C)}$ with $C\in \Theta ^-(n)_r$ , $\textrm {deg}(C)=\textrm { deg}(\mathbf {x}_j^{\mathbf {f}} \mathbf {x}_1^\prime )$ . Therefore, by Lemma 4.7 each $\mathbf {x}_1 \mathbf {k}_{{\lambda }'} \mathbf {x}_j^{\mathbf {e}}\mathbf {h}_j \mathbf {x}^{\mathbf {f}}_j\mathbf {x}_1^\prime $ is a -linear combination of $\mathbf {m}^{(A',\mu )}$ with $\textrm {deg}(A')<\textrm {deg}(A)$ , since $\textrm {deg}(\mathbf {x}_1)+\textrm {deg}(\mathbf {x}_j^{\mathbf {e}})+\textrm {deg}(\mathbf {x}^{\mathbf {f}}_j)+\textrm {deg}(\mathbf {x}_1')<\textrm {deg}(A)$ . Consequently, by induction, we have . The proof is completed.
By Lemma 3.5, we have Therefore, the map given in (3.7) restricts to a surjective algebra homomorphism
By (3.8), we have
for ${\lambda }\in \Lambda (n,d)$ . So, we have $\zeta _{d,r} (I_{d,r})=0$ . Hence, the map induces a surjective algebra homomorphism
Theorem 4.10. The map $\zeta _{d,r}^{\prime }$ is an algebra isomorphism. In particular, the kernel of the map is generated by the elements $1-\sum _{\mu \in \Lambda (n,d)} K_{\mu }$ , $K_{i} K_{\lambda }-\varepsilon ^{\lambda _{i}} K_{\lambda }$ and $\big [{K_i;0 \atop t}\big ] K_{\lambda }-\big [{{\lambda }_i \atop t}\big ]_{\varepsilon } K_{\lambda }$ for $1 \leqslant i \leqslant n$ , $t \in \mathbb {N}$ and $\lambda \in \Lambda (n,d)$ .
5 The algebra
For $d\in \mathbb N$ , let
where $J_{d,r}$ is the two-sided ideal of generated by the elements $1_{\lambda }$ for $\lambda \notin \Lambda (n,d)$ . For ${\lambda }\in \mathbb Z^{n}$ , let
Then, we have $1=\sum _{{\lambda }\in \Lambda (n,d)}\mathfrak {k}_{\lambda }$ . For $1\leqslant i\leqslant n-1$ and $0\leqslant m<lp^{r-1}$ , let
For $A\in \Theta ^\pm (n)_r$ , let. Furthermore for $1\leqslant i\leqslant n$ , $1\leqslant j\leqslant n-1$ , $c\in\mathbb{Z}$ and $t\in\mathbb{N}$ let
We will prove in Theorem 5.5 that the algebra is isomorphic to the infinitesimal q-Schur algebra .
By [Reference Beilinson, Lusztig and MacPherson3, Lem. 3.10 and Prop. 4.2], we have the following result.
Lemma 5.1. There is an unique algebra antiautomorphism $\dot \tau _d$ on such that $\dot \tau _d(\mathfrak {e}_i^{(m)})=\mathfrak {f}_i^{(m)}$ , $\dot \tau _d(\mathfrak {f}_i^{(m)})=\mathfrak {e}_i^{(m)}$ and $\dot \tau _d(\mathfrak {k}_{\lambda })=\mathfrak {k}_{\lambda }$ for $1\leqslant i\leqslant n-1$ , $0\leqslant m<lp^{r-1}$ and ${\lambda }\in \Lambda (n,d)$ .
Clearly we have the following result.
Lemma 5.2. Let $1 \leqslant i \leqslant n, 1\leqslant j\leqslant n-1$ , $c\in \mathbb Z$ , $t\in \mathbb N$ and $\lambda \in \mathbb {Z}^{n}$ . The following formulas hold in
Recall from (3.1) that $\Theta ^\pm (n)_r=\{A\in \Theta ^\pm (n) \mid 0 \leqslant a_{ij} < lp^{r-1}, \forall i \neq j\} $ , $\Theta ^+(n)_r=\{A\in \Theta ^+(n) \mid 0 \leqslant a_{ij} < lp^{r-1}, \forall i < j \}$ and $\Theta ^-(n)_r=\{A\in \Theta ^-(n) \mid 0 \leqslant a_{ij} < lp^{r-1}, \forall i> j \}$ .
Lemma 5.3. Let $\lambda \in \Lambda (n,d)$ . The following results hold in . (1) If $A \in \Theta ^+(n)_r$ and $\lambda _{i}<\sigma _{i}(A)$ for some i, then $\mathfrak {e}^{(A)}\mathfrak {k}_{\lambda } =0$ . (2) If $A \in \Theta ^-(n)_r$ and $\lambda _{i}<\sigma _{i}(A)$ for some i, then $\mathfrak {k}_{\lambda }\mathfrak {f}^{(A)}=0$ .
Proof. Assume $A\in \Theta ^+(n)_r$ and ${\lambda }_i<\sigma _i(A)$ for some i. For $\mu \in \mathbb Z^{n}, 1 \leqslant j \leqslant n-1$ , we have $\mathfrak {e}_j\mathfrak {k}_\mu =\mathfrak {k}_{\mu +\alpha _j} \mathfrak {e}_j$ . This implies that
where $\mathfrak {m}_{j} =\mathfrak {e}_{j-1}^{(a_{j-1, j})}(\mathfrak {e}_{j-2}^{(a_{j-2, j})} \mathfrak {e}_{j-1}^{(a_{j-2, j})}) \cdots (\mathfrak {e}_{1}^{(a_{1, j})} \mathfrak {e}_{2}^{(a_{1, j})} \cdots \mathfrak {e}_{j-1}^{(a_{1, j})})$ and
Thus, we have $ {\mathfrak {e}^{(A)}\mathfrak {k}_{\lambda }}= {\mathfrak {m}_n \mathfrak {m}_{n-1} \cdots \mathfrak {m}_{i+1} \mathfrak {k}_{{\lambda }+\nu } \mathfrak {m}_i \mathfrak {m}_{i-1} \cdots \mathfrak {m}_2 }.$ Since ${\lambda }_i<\sigma _i(A)$ , we have ${\lambda }+\nu \not \in \Lambda (n,d)$ . It follows that $\mathfrak {k}_{{\lambda }+\nu }=0$ . Therefore, we have $\mathfrak {e}^{(A)}\mathfrak {k}_{\lambda }=0$ . Applying $\dot \tau _d$ to the identity in (1) gives that in (2).
Proposition 5.4. Let ${\mathfrak M}_{d,r}=\{\mathfrak {e}^{(A^+)}\mathfrak {k}_{\lambda }\mathfrak {f}^{(A^-)} \mid A \in \Theta ^\pm (n)_r,\, \lambda \in \Lambda (n,d),\, \lambda \geqslant {\boldsymbol \sigma }(A) \}$ . Then, the algebra is spanned as a -module by the elements in ${\mathfrak M}_{d,r}$ .
Proof. By Proposition 3.3, we have
Thus, it is enough to prove that if ${\lambda } \in \Lambda (n,d)$ and $ {\lambda }_i <\sigma _i(A) $ for some i, . We apply induction on $\textrm {deg}(A)$ . If $\textrm {deg}(A)=1$ , then by Lemma 5.3 we have $\mathfrak {e}^{(A^+)}\mathfrak {k}_{\lambda }\mathfrak {f}^{(A^-)}=0$ . Now suppose $\textrm {deg}(A)>1$ . For $2\leqslant j\leqslant n$ let
Then, we have
where $X_1=\mathfrak {m}_n\mathfrak {m}_{n-1}\cdots \mathfrak {m}_{i+1}$ , $X_2=\mathfrak {m}_i\mathfrak {m}_{i-1}\cdots \mathfrak {m}_2$ , $Y_1=\mathfrak {m}_2^{\prime }\mathfrak {m}_3^{\prime }\cdots \mathfrak {m}_i^{\prime }$ , $Y_2=\mathfrak {m}_{i+1}^{\prime }\mathfrak {m}_{i+2}^{\prime }\cdots \mathfrak {m}_{n}^{\prime }$ and
By Lemma 2.1 and 5.2, we have $\mathfrak {k}_{{\lambda }'}X_2Y_1=\mathfrak {k}_{{\lambda }'}Y_1X_2+\mathfrak {k}_{{\lambda }'}f_1f_2$ where $f_1$ is a -linear combination of monomials $f_{1,k}$ in the $\mathfrak {e}_s^{(a)}$ , $f_{2}$ is a -linear combination of monomials $f_{2,k}$ in the $\mathfrak {f}_s^{(a)}$ , and $\textrm {deg}(f_{1,k})+\textrm {deg}(f_{2,k})<\textrm {deg}(X_2)+\textrm {deg}(Y_1)$ . Since ${\lambda }_i<\sigma _i(A)$ , we have ${\lambda }_i^{\prime }<\sigma _i(A^-)$ . Hence by Lemma 5.3, we have $\mathfrak {k}_{{\lambda }'}Y_1=0$ . This implies that
where
By Proposition 3.1, we have and . Thus,
By induction, we have for $B\in \Theta ^\pm (n)_r$ with $\textrm {deg}(B)<\textrm {deg}(A)$ . Therefore, .
By Lemma 3.6, we have Therefore, the map given in (3.10) restricts to a surjective algebra homomorphism
Since $\dot {\zeta }_{d,r} (J_{d,r})=0$ , the map induces a surjective algebra homomorphism
A presentation of was given in [Reference Fu16, Th. 3.9] in the case where $r=1$ , is a field and $l'$ is odd. We now generalize this result to the general case.
Theorem 5.5. The map is an algebra isomorphism. In particular, the kernel of the map is generated by the elements $1_{\lambda }$ for $\lambda \notin \Lambda (n,d)$ .
6 The classical case
Let ${\mathcal U}(\mathfrak {gl}_n)$ be the $\mathbb Q$ -algebra defined by the generators
and the relations
-
(a) $H_iH_j=H_jH_i;$
-
(b) $H_{i}\bar E_j-\bar E_jH_i=(\delta _{i,j}-\delta _{i,j+1}) \bar E_j;$
-
(c) $H_{i}\bar F_j-\bar F_jH_i=(-\delta _{i,j}+\delta _{i,j+1}) \bar F_j;$
-
(d) $ \bar E_i\bar E_j=\bar E_j\bar E_i,\ \bar F_i\bar F_j=\bar F_j\bar F_i\ when\ |i-j|>1;$
-
(e) $\bar E_i\bar F_j-\bar F_j\bar E_i=\delta _{i,j}H_i;$
-
(f) $ \bar E_i^2\bar E_j-2\bar E_i\bar E_j\bar E_i+\bar E_j\bar E_i^2=0\ when\ |i-j|=1;$
-
(g) $ \bar F_i^2\bar F_j-2\bar F_i\bar F_j\bar F_i+\bar F_j\bar F_i^2=0\ when\ |i-j|=1.$
Then, ${\mathcal U}(\mathfrak {gl}_n)$ is the universal enveloping algebra of $\mathfrak {gl}_n$ . Let ${\mathcal U}_{\mathbb Z}(\mathfrak {gl}_n)$ be the $\mathbb Z$ -subalgebra of ${\mathcal U}(\mathfrak {gl}_n)$ generated by $\bar E_i^{(m)}$ , $\bar F_i^{(m)}$ , and $\big ({H_j\atop t}\big )$ for $1\leqslant i\leqslant n-1$ , $1\leqslant j\leqslant n$ and $m,t\in \mathbb N$ , where
Let ${U_{\mathbb Z}(\mathfrak {gl}_n)}={U_{\mathcal Z}(\mathfrak {gl}_n)}\otimes _{\mathcal Z}\mathbb Z$ , where $\mathbb Z$ is viewed as ${\mathcal Z}$ -modules by specializing v to $1$ . Let ${\bar U_{\mathbb Z}(\mathfrak {gl}_n)}={U_{\mathbb Z}(\mathfrak {gl}_n)}/\langle K_i-1\mid 1\leqslant i\leqslant n\rangle $ . We shall denote the images of $E_i^{(m)}$ , $F_i^{(m)}$ , etc. in ${\bar U_{\mathbb Z}(\mathfrak {gl}_n)}$ by the same letters. By [Reference Lusztig22, 6.7(c)], there is an algebra isomorphism
such that $\theta (E_i^{(m)})=\bar E_i^{(m)}$ , $\theta (F_i^{(m)})=\bar F_i^{(m)}$ , $\theta (\big [{K_j;0\atop t}\big ])=\big ({H_j\atop t}\big )$ for $1\leqslant i\leqslant n-1$ , $1\leqslant j\leqslant n$ , $m,t\in \mathbb N$ . We will identify ${\bar U_{\mathbb Z}(\mathfrak {gl}_n)}$ with ${\mathcal U}_{\mathbb Z}(\mathfrak {gl}_n)$ .
Let ${\mathcal S}_{\mathbb Z}(n,d)={\mathcal S}_{\mathcal Z}(n,d)\otimes _{\mathcal Z}\mathbb Z$ where $\mathbb Z$ is viewed as ${\mathcal Z}$ -modules by specializing v to $1$ . The map $\zeta _{d}$ given in (3.6) induces, upon tensoring with $\mathbb Z$ , a surjective algebra homomorphism
Since $\xi _{d}(K_i)=1$ , the map $\xi _{d}$ induces a surjective algebra homomorphism
In the remainder of this section, we assume that $l'=l=1$ . Let
We shall denote the images of $\bar E_{i}^{(m)}$ , $\bar F_{i}^{(m)}$ , etc. in by the same letters. For $A\in {\Theta (n,d)}$ , let $[A]_1$ be the image of $[A]$ in . The map $\xi _{d}$ induces, upon tensoring with , a surjective algebra homomorphism
Let be the infinitesimal Schur algebra introduced in [Reference Doty, Nakano and Peters11]. By [Reference Doty, Nakano and Peters11, (5.3.4)], the set $\{[A]_1\mid A\in {\Theta (n,d)},\,a_{i,j}<p^r,\,\forall i,j\}$ forms a -basis for . Hence, we have
Let be the -subalgebra of generated by the elements $\bar E_i^{(m)}$ , $\bar F_i^{(m)}$ , $\big ({H_j\atop t}\big )$ for $1\leqslant i\leqslant n-1$ , $1\leqslant j\leqslant n$ , $t\in \mathbb N$ and $0\leqslant m<p^{r}$ . Then, by (6.1), we have
Therefore, by Lemma 3.5, we have . Hence, by restricting the map $\xi _{d}$ to , we obtain a surjective algebra homomorphism
By Theorem 4.10, we obtain the following result.
Theorem 6.1. The kernel of the map is generated by the elements $1-\sum _{\mu \in \Lambda (n,d)} H_{\mu }$ and $\big ({H_i \atop t}\big ) H_{\lambda }-\big ({{\lambda }_i \atop t}\big ) H_{\lambda }$ for $1 \leqslant i \leqslant n$ , $t \in \mathbb {N}$ and $\lambda \in \Lambda (n,d)$ , where $H_{\lambda }=\prod _{1\leqslant i\leqslant n}\big ({H_i\atop {\lambda }_i}\big ).$
Let
where
$H^{\mathbf {j}}=\prod _{1\leqslant i\leqslant n} H_i^{j_i}$ and ${\lambda }^{{\mathbf {j}}}=\prod _{1\leqslant i\leqslant n}{\lambda }_i^{j_i}$ . Let $\bar \pi _{{\lambda },\mu }:{\mathcal U}(\mathfrak {gl}_n)\rightarrow {}_{\lambda }{\mathcal U}(\mathfrak {gl}_n)_\mu $ be the canonical projection. Let $\bar 1_{\lambda }=\bar \pi _{{\lambda },{\lambda }}(1)$ . As in the case of $\dot {{{\mathbf {U}}}}(\mathfrak {gl}_n)$ , there is a natural associative $\mathbb Q$ -algebra structure on $\dot {\mathcal U}(\mathfrak {gl}_n)$ inherited from that of ${\mathcal U}(\mathfrak {gl}_n)$ , and $\dot {\mathcal U}(\mathfrak {gl}_n)$ is naturally a ${\mathcal U}(\mathfrak {gl}_n)$ -bimodule. Let $\dot {\mathcal U}_{\mathbb Z}(\mathfrak {gl}_n)$ be the $\mathbb Z$ -subalgebra of $\dot {\mathcal U}(\mathfrak {gl}_n)$ generated by the elements $\bar E_i^{(m)}\bar 1_{\lambda }$ and $\bar 1_{\lambda }\bar F_i^{(m)}$ for $1\leqslant i\leqslant n-1$ , ${\lambda }\in \mathbb Z^{n}$ and $m\in \mathbb N$ .
Let ${\dot U_{\mathbb Z}(\mathfrak {gl}_n)}=\dot {{U}}_{\mathcal Z}(\mathfrak {gl}_n)\otimes _{\mathcal Z}\mathbb Z$ , where $\mathbb Z$ is viewed as a ${\mathcal Z}$ -module by specializing v to $1$ . By (6.1), we have
We will identify ${\dot U_{\mathbb Z}(\mathfrak {gl}_n)}$ with $\dot {\mathcal U}_{\mathbb Z}(\mathfrak {gl}_n)$ . The map $\dot {\zeta }_{d}$ given in (3.9) induces, upon tensoring with $\mathbb Z$ , a surjective algebra homomorphism
Let . We shall denote the images of $\bar E_{i}^{(m)}\bar 1_{\lambda }$ , $\bar 1_{\lambda }\bar F_{i}^{(m)}$ in by the same letters. The map $\dot \xi _{d}$ induces, upon tensoring with , a surjective algebra homomorphism
Let be the -subalgebra of generated by the elements $\bar E_i^{(m)}\bar 1_{\lambda }$ , $\bar 1_{\lambda }\bar F_i^{(m)}$ for $1\leqslant i\leqslant n-1$ , ${\lambda }\in \mathbb Z^{n}$ and $0\leqslant m<p^{r}$ . Then, by (6.2), we have
By Lemma 3.6, we have . Hence, by restricting the map $\dot {\xi }_{d}$ to , we obtain a surjective algebra homomorphism
By Theorem 5.5, we obtain the following result.
Theorem 6.2. The kernel of the map is generated by the elements $\bar 1_{\lambda }$ for ${\lambda }\not \in \Lambda (n,d)$ .
7 Borel subalgebras of the infinitesimal q-Schur algebra
In this section, we investigate Borel subalgebras of the infinitesimal q-Schur algebra . In what follows, we focus entirely on the quantum case as the corresponding results for the classical cases are essentially the same.
Let and . These algebras are called Borel subalgebras of . Furthermore, let (resp. ) be the -subalgebra of generated by the elements $E_{i}^{(m)}1_{\lambda }$ (resp. $1_{\lambda } F_{i}^{(m)}$ ) for $1\leqslant i\leqslant n-1$ , ${\lambda }\in \mathbb Z^{n}$ and $0\leqslant m<lp^{r-1}$ .
Let (resp. ) be the -subalgebra of generated by $\mathtt {e}_i^{(m)}$ (resp. $\mathtt {f}_i^{(m)}$ ) and $\mathtt {k}_\lambda $ for $1 \leqslant i \leqslant n-1$ , $0\leqslant m<lp^{r-1}$ and $\lambda \in \Lambda (n,d)$ . These algebras are called Borel subalgebras of .
Let (resp. ) be the -subalgebra of generated by $\mathtt {e}_i^{(m)}$ (resp. $\mathtt {f}_i^{(m)}$ ) for $1\leqslant i\leqslant n-1$ and $0\leqslant m<lp^{r-1}$ .
Lemma 7.1. Each of the following set forms a -basis of :
-
(1) ${\mathscr M}_{d,r}^+:=\{\mathtt {e}^{(A)} \mid A \in \Theta ^+(n)_r,\,\sigma (A)\leqslant d\}$ ;
-
(2) ${\mathscr P}_{d,r}^+:=\{A(\mathbf {0},d)\mid A\in \Theta ^+(n)_r,\,\sigma (A)\leqslant d\}$ .
A similar result holds for .
Proof. By [Reference Doty and Giaquinto8, Prop. 8.2], we have $1=\sum _{{\lambda }\in \Lambda (n,d)}\mathtt {k}_{\lambda }$ . Hence, by [Reference Du and Parshall15, Lem. 4.10], we have
for $A\in \Theta ^+(n)_r$ . Furthermore, we have
for $A\in \Theta ^+(n)_r$ , since $1=\sum _{{\lambda }\in \Lambda (n,d)}[\operatorname {diag}({\lambda })]_{\varepsilon }$ . Therefore, we have
for $A\in \Theta ^+(n)_r$ with $\sigma (A)>d$ . Hence, by Proposition 3.1 and 3.2, we conclude that . Furthermore, by Proposition 3.7, the sets ${\mathscr M}_{d,r}^+$ and ${\mathscr P}_{d,r}^+$ are both linearly independent. Our assertion follows.
Lemma 7.2. Each of the following set forms a -basis of :
-
(1) ${\mathscr M}_{d,r}^{\geqslant 0}:=\{{\mathtt e}^{(A)}\mathtt {k}_\lambda \mid A \in \Theta ^+(n)_r,\,{\lambda }\in \Lambda (n,d),\, \lambda \geqslant {\boldsymbol \sigma }(A)\}$ ;
-
(2) ${\mathscr L}_{d,r}^{\geqslant 0}:= \{[A+\operatorname {diag}({\lambda })]_{\varepsilon } \mid A \in \Theta ^+(n)_r,\, {\lambda }\in \Lambda (n,d-\sigma (A)) \}$ .
A similar result holds for .
Proof. From Lemma 7.1, (7.1) and (7.2), it follows that . Therefore, the result follows from Proposition 3.7.
Let be the quotient of by $I_{d,r}^{\geqslant 0}$ , where $I_{d,r}^{\geqslant 0}$ is the two-sided ideal of generated by the elements $1-\sum _{\mu \in \Lambda (n,d)} K_{\mu }, K_{i} K_{\lambda }-\varepsilon ^{\lambda _{i}} K_{\lambda }$ and $\big [{K_i;0 \atop t}\big ] K_{\lambda }-\big [{{\lambda }_i \atop t}\big ]_{\varepsilon } K_{\lambda }$ for $1 \leqslant i \leqslant n$ , $t \in \mathbb {N}$ and $\lambda \in \Lambda (n,d)$ .
By restricting the map $\zeta _{d,r}$ given in (4.2) to , we obtain a surjective algebra homomorphism . Since $\zeta _{d,r}(I_{d,r}^{\geqslant 0})=0$ , the map $\zeta _{d,r}$ induces an epimorphism
Theorem 7.3. The map is an algebra isomorphism. In particular, the kernel of the map is $I_{d,r}^{\geqslant 0}$ . A similar result holds for .
Proof. Using an argument similar to the proof of Proposition 4.9, we can show that the algebra is spanned as a -module by the elements $E^{(A)} K_{\lambda }+I_{d,r}^{\geqslant 0}$ for $A \in \Theta ^+(n)_r$ , $\lambda \in \Lambda (n,d)$ and $\lambda \geqslant {\boldsymbol \sigma }(A)$ . Furthermore, by Lemma 7.2, the set
forms a -basis for . Hence, $\zeta _{d,r}' $ is an algebra isomorphism.
Let be the quotient of by $J_{d,r}^{\geqslant 0}$ , where $J_{d,r}^{\geqslant 0}$ is the two-sided ideal of generated by the elements $1_{\lambda }$ for $\lambda \not \in \Lambda (n,d)$ .
By restricting the map $\dot {\zeta }_{d,r}$ given in (5.1) to , we obtain a surjective algebra homomorphism . Since $\dot {\zeta }_{d,r}(J_{d,r}^{\geqslant 0})=0$ , the map $\dot {\zeta }_{d,r}$ induces an epimorphism
Theorem 7.4. The map is an algebra isomorphism. In particular, the kernel of the map is $J_{d,r}^{\geqslant 0}$ . A similar result holds for .
Proof. Using an argument similar to the proof of Proposition 5.4, we can show that the algebra is spanned as a -module by the elements $E^{(A)}1_{\lambda }+J_{d,r}^{\geqslant 0}$ for $A\in \Theta ^+(n)_r$ , ${\lambda } \in \Lambda (n,d)$ and ${\lambda } \geqslant {\boldsymbol \sigma }(A)$ . Furthermore, by Lemma 7.2, the set
forms a -basis of . Therefore, $\dot {\zeta }_{d,r}'$ is an algebra isomorphism.
8 Irreducible -modules
In this section, we assume that is a field, $p>0$ and $l'=l$ is odd. Let $X=\mathbb Z^{n}$ and $X^+=\{{\lambda }\in X\mid {\lambda }_1\geqslant {\lambda }_{2}\geqslant \cdots \geqslant {\lambda }_n\}$ . For ${\lambda }\in X^+$ , let $L({\lambda })$ be the simple integrable -module of highest weight ${\lambda }$ . Let $\text {Ind}^{U_2}_{U_1}(-)= H^0(U_2/U_1,-)$ be the induction functor for quantized enveloping algebras defined in [Reference Andersen, Polo and Wen1], [Reference Andersen, Polo and Wen2].
For ${\lambda }\in X$ , let
Let $P_r=\{{\lambda }\in \mathbb N^{n}\mid 0\leqslant {\lambda }_i-{\lambda }_{i+1}<lp^{r-1}\text { for }1\leqslant i\leqslant n \}$ , where ${\lambda }_{n+1}=0$ . The following result was given in [Reference Drupieski12, Ths. 3.4.1 & 3.4.3].
Theorem 8.1. $(1)$ The set $\{\widehat L_r({\lambda })\mid {\lambda }\in X\}$ form a complete set of pairwise nonisomorphic irreducible integrable -modules.
$(2)$ For ${\lambda },\mu \in X$ , we have $\widehat L_r({\lambda }+lp^{r-1}\mu )\cong \widehat L_r({\lambda })\otimes lp^{r-1}\mu $ .
$(3)$ For ${\lambda }\in P_r$ , we have .
If M is a -module and ${\lambda }\in X$ let
Let ${\Gamma }_r=P_r+lp^{r-1}\mathbb N^{n}$ and ${\Gamma }_r^d=\big \{{\lambda }\in {\Gamma }_r\big |\sum _{i=1}^n{\lambda }_i=d\big \}.$ For ${\lambda },\mu \in \mathbb Z^{n}$ with $\sum _{1\leqslant i\leqslant n}{\lambda }_i=\sum _{1\leqslant i\leqslant n}\mu _i$ we write ${\lambda }\trianglelefteq \mu $ if $\sum _{1\leqslant s\leqslant i}{\lambda }_s\leqslant \sum _{1\leqslant s\leqslant i}\mu _s$ for $1\leqslant i\leqslant n$ .
Lemma 8.2. For ${\lambda }\in {\Gamma }_r^d$ we have $\widehat L_r({\lambda })=\oplus _{\mu \in \Lambda (n,d)}\widehat L_r({\lambda })_\mu $ .
Proof. We write ${\lambda }=\alpha +lp^{r-1}\beta $ with $\alpha \in P_r$ and $\beta \in \mathbb N^{n}$ . By Theorem 8.1, we have $\widehat L_r({\lambda })\cong L(\alpha )\otimes lp^{r-1}\beta .$ Hence, it suffices to show that $L(\alpha )=\oplus _{\mu \in \Lambda (n,d')}L(\alpha )_\mu $ , where $d'=\sum _{1\leqslant i\leqslant n}\alpha _i$ . If $L(\alpha )_\mu \not =0$ for some $\mu \in \mathbb Z^{n}$ with $\sum _{1\leqslant i\leqslant n}\mu _i=d'$ . We claim that $\mu \in \mathbb N^{n}$ . Otherwise, there exists some element w in the symmetric group $\mathfrak {S}_n$ such that $\gamma =(\mu _{w(1)},\ldots ,\mu _{w(n)})$ and $\gamma _n<0$ . Since $L(\alpha )_\mu \not =0$ , we have $L(\alpha )_{\gamma }\not =0$ and hence ${\gamma }\unlhd \alpha $ . This implies that $\sum _{1\leqslant i\leqslant n-1}\gamma _i\leqslant \sum _{1\leqslant i\leqslant n-1}\alpha _i\leqslant d'$ . Hence, since ${\gamma }_n<0$ , we have $\sum _{1\leqslant i\leqslant n}\gamma _i<d'$ . This is a contradiction. The assertion follows.
The irreducible modules for infinitesimal q-Schur algebras were classified in [Reference Cox4, Sec. 5.1]. We now use Theorem 4.10 to give a classification of irreducible -modules.
Theorem 8.3. The set $\{\widehat L_r({\lambda })\mid {\lambda }\in {\Gamma }_r^d\}$ forms a completed set of pairwise nonisomorphic irreducible -modules.
Proof. Let ${\lambda }\in {\Gamma }_r^d$ . By Lemma 8.2, we have $\widehat L_r({\lambda })=\oplus _{\mu \in \Lambda (n,d)}\widehat L_r({\lambda })_\mu $ . Let $w_\mu $ be a nonzero vector in $\widehat L_r({\lambda })_\mu $ for some $\mu \in \Lambda (n,d)$ . Since $\mu \in \Lambda (n,d)$ , we have $K_\alpha w_\mu =\big [{\mu \atop \alpha }\big ]_{\varepsilon } w_\mu =\delta _{\alpha ,\mu }w_\mu $ for $\alpha \in \Lambda (n,d)$ . It follows that
for $\alpha \in \Lambda (n,d)$ , $1\leqslant i\leqslant n$ and $t\in \mathbb N$ . Thus, by Theorem 4.10, we conclude that $\widehat L_r({\lambda })$ can be regarded as a -module.
On the other hand, let L be an irreducible -module. By Theorem 8.1, we conclude that $L\cong \widehat L_r(\nu +lp^{r-1}\delta )\cong L(\nu )\otimes lp^{r-1}\delta $ for some $\nu \in P_r$ and $\delta \in \mathbb Z^{n}$ . Hence, since L is a -module, we have $(\nu _{w(1)},\nu _{w(2)},\ldots ,\nu _{w(n)})+ lp^{r-1}\delta \in \Lambda (n,d)$ for any w in the symmetric group ${\mathfrak S}_n$ . It follows that $\nu _n+lp^{r-1}\delta _j\geqslant 0$ for $1\leqslant j\leqslant n$ . Furthermore, since $\nu \in P_r$ , we have $0\leqslant \nu _n<lp^{r-1}$ . Therefore, we have $\delta _j\geqslant 0$ for $1\leqslant j\leqslant n$ . Consequently, we have $\nu +lp^{r-1}\delta \in {\Gamma }_r^d$ . The proof is completed.
Acknowledgement
Supported by the National Natural Science Foundation of China (12371032, 12431002).